Desain Model Database Layanan Panti Werdha dengan Menerapkan Metode Database Life Cycle - Stefanus Setyo Wibagso; Enjel Lia (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
A nursing home is a place where the elderly get care services to live out their parenthood. In the management of nursing homes, many activities are carried out such as nursing services for the elderly, family visit activities, receiving donor assistance, managing elderly contributions, and transferring the elderly. Most of the information about these activities is still referred to manually and some of it is processed using separate applications. The aim of this research is to design the database model needed by the nursing home. The database model design can later be used as a reference for software developers in building an integrated nursing home information system. The form of research carried out is in the form of case studies with data collection methods through interview techniques and documentation studies. Meanwhile, for the analysis and design of the database model itself, it uses Database Life Cycle (DBLC) method which focuses on conceptual database design, logical database design, and physical database design. The result of this design is a relational database consisting of 11 tables and 12 relations. This research is a development from previous research with the same type where the previous research produced 7 tables with 6 relations.